2011
DOI: 10.1007/s00203-011-0758-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HrpX regulon genes in Xanthomonas oryzae pv. oryzicola using a GFP visualization technique

Abstract: Xanthomonas oryzae pv. oryzicola is the causal agent of bacterial leaf streak in rice and injects repertoires of T3S effectors (T3SEs), which are normally regulated by a global regulator HrpX, into plant cells to suppress plant innate immunity for disease development. To establish a visualization technique to identify HrpX regulon genes in this pathogen, we chose six known or unknown T3SE genes of X. oryzae pv. oryzicola (strain RS105) as the targets in this report. The promoters of these candidates, whether o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…However, the mutation either in the hrpG gene, encoding a protein belonging to the OmpR family of two-component regulatory systems and activating the expression of hrpA and hrpX (Wengelnik et al, 1996), or in the hrpX gene, encoding an AracC-type transcriptional activator in regulation of the expression of the hrpB to hrpF operons for theT3SS (Li et al, 2011(Li et al, , 2012, did not impair the expression of EcpA Xoc (data not shown). Indeed, in the promoter region of ecpA Xoc there is no plant-inducible promoter (PIP)-box characteristic of HrpX regulon genes (Tsuge et al, 2005;Furutani et al, 2009;Li et al, 2012). This implies that Xoc EcpA is HrpG-and HrpX-independent, which is different from some, but not all, CWDEs in other Xanthomonas species.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the mutation either in the hrpG gene, encoding a protein belonging to the OmpR family of two-component regulatory systems and activating the expression of hrpA and hrpX (Wengelnik et al, 1996), or in the hrpX gene, encoding an AracC-type transcriptional activator in regulation of the expression of the hrpB to hrpF operons for theT3SS (Li et al, 2011(Li et al, , 2012, did not impair the expression of EcpA Xoc (data not shown). Indeed, in the promoter region of ecpA Xoc there is no plant-inducible promoter (PIP)-box characteristic of HrpX regulon genes (Tsuge et al, 2005;Furutani et al, 2009;Li et al, 2012). This implies that Xoc EcpA is HrpG-and HrpX-independent, which is different from some, but not all, CWDEs in other Xanthomonas species.…”
Section: Discussionmentioning
confidence: 94%
“…To investigate the possibility that EcpB (AEQ97125.1) plays a role in the extracellular proteolytic activity in Xoc, this gene (XOC_3026) was deleted using the suicide vector pKMS1 (Zou et al, 2011a;Li et al, 2012). Two fragments flanking the ecpB gene, ecpB1 (348 bp) and ecpB2 (504 bp), were amplified from strain RS105 genomic DNA using the primer pairs ecpB1-F/ecpB1-R and ecpB2-F/ecpB2-R (Table S3), respectively.…”
mentioning
confidence: 99%
“…oryzicola abolishes the elicitation of HR in tobacco and pathogenicity in rice [8]. Thus, we assumed that the expression of HR-eliciting genes, including hpa1 , are also regulated by HrpG and HrpX [60]. Using cDNA microarrays of X. oryzae pv.…”
Section: Resultsmentioning
confidence: 99%
“…In Hrp group II, the cis -acting PIP-box promoter is followed by a −10 box, and collectively these elements indicate regulation via HrpX [76], [79], [89]. However, the PIP-box in ssb X genes is not followed by the −10 box, possibly because proteins in addition to HrpX are involved in regulation [44], [60]. At the amino acid level, harpin proteins possess T3SS signals that are characterized by at least 20% Pro and Ser residues in the first 50 amino acids at the N-terminus; this protein signature is required for secretion through the T3SS [78], [90].…”
Section: Discussionmentioning
confidence: 99%
“…In Xanthomonas, HrpG and HrpX form a regulatory cascade in which HrpG regulates the expression of the hrpA operon and hrpX. HrpX subsequently activates the expression of PIP box-containing hrp transcripts (hrpB to hrpF) Wengelnik et al, , 1999) and other HrpX-regulated genes (Furutani et al, 2009;Jiang et al, 2009b;Li et al, 2012). Another cis element resembling the -10 binding sequence (YANNRT: Y, C/T; N, A/T/G/C; R, A/G) of RNA polymerase 70 factor is present 30-32 bp downstream of the PIP box in Xoo (Furutani et al, 2006).…”
Section: Introductionmentioning
confidence: 99%